Design and Analysis of Secure and Dependable Automotive CPS: A Steer-by-Wire Case Study - Munir, Arslan; Koushanfar, Farinaz (IEEE transactions on dependable and secure computing, 2020)
The next generation of automobiles (also known as cybercars) will increasingly incorporate electronic control units (ECUs) in novel automotive control applications. Recent work has demonstrated the vulnerability of modern car control systems to security attacks that directly impacts the cybercar's physical safety and dependability. In this paper, we provide an integrated approach for the design of secure and dependable automotive cyber-physical systems (CPS) using a case study: a steer-by-wire (SBW) application over controller area network (CAN). The challenge is to embed both security and dependability over CAN while ensuring that the real-time constraints of the automotive CPS are not violated. Our approach enables early design feasibility analysis of automotive CPS by embedding essential security primitives (i.e., confidentiality, integrity, and authentication) over CAN subject to the real-time constraints imposed by the desired quality of service and behavioral reliability. Our method leverages multicore ECUs for providing fault tolerance by redundant multi-threading (RMT) and also further enhances RMT for quick error detection and correction. We quantify the error resilience of our approach and evaluate the interplay of performance, fault tolerance, security, and scalability for our SBW case study.